A study on correlation between bleeding pattern and histopathological findings of endometrium among perimenopausal women - Nair, Radha; M., Mallikarjuna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: During climacteric, ovarian activity declines. Initially, ovulation fails, no corpus luteum forms, and no progesterone are secreted by the ovary. Therefore the premenopausal menstrual cycles are shortened, often anovulatory and irregular. The irregularity in menstrual cycle during perimenopause can be due to anovulation or to irregular maturation of follicles. Methods: The endometrial samples (endometrial curettage/ biopsy and hysterectomy specimens) sent to pathology laboratory were analyzed. These specimens are fixed in 10% formalin and gross morphology was recorded. Endometrial samples were totally embedded and representative bits are taken from hysterectomy specimens. These bits were placed in cassettes and kept in fixative and processed in the automatic tissue processor. Paraffin tissue blocks were prepared and 3-4 micrometer thick sections were cut and stained with routine haematoxylin and eosin. A detailed histological study was carried out and the findings were noted. Results: Among total study subjects, 62% of patient’s endometrium was in proliferative phase, 26% of patient’s endometrium was in secretory phase, 6% of patient’s endometrium was in cystoglandular hyperplasia. Dysplasia with atypical changes was found in 2% of patients. Adenomatous polyp was found in 2% of patients. Simple hyperplasia was found in 2% of patients. Conclusions: Patients with abnormal uterine bleeding should always be subjected to histopathological investigation.